2016
DOI: 10.1111/andr.12177
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone deficiency in testicular cancer survivors – a systematic review and meta‐analysis

Abstract: SUMMARYResults concerning treatment of Testicular Germ Cell Cancer (TGCC) and subsequent risk of testosterone deficiency are conflicting. To systematically evaluate and estimate the risk of testosterone deficiency (TD) in TGCC-patients according to treatment to optimize follow-up and for prevention of late effects related to hypogonadism. We performed a critical review of PubMed in January 2015 according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) statement. Twelve publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 51 publications
0
42
0
3
Order By: Relevance
“…Several factors such as small testicular size and presence of microlithiasis (Eberhard et al, 2008;P€ uhse et al, 2011), biochemical Leydig cell dysfunction at the time of diagnosis (Bandak et al, 2017c;Eberhard et al, 2008) and chemotherapy and radiotherapy have been associated with long-term risk of Leydig cell dysfunction and manifest testosterone deficiency in patients with TGCC (Bandak et al, 2016). In the present study, ultrasonic size of testicle without a tumour evaluated at the follow-up was significantly smaller in patients with LCH, while there was no difference in the prevalence of microlithiasis among patients with or without LCH.…”
Section: Orchiectomy Alone Bep Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors such as small testicular size and presence of microlithiasis (Eberhard et al, 2008;P€ uhse et al, 2011), biochemical Leydig cell dysfunction at the time of diagnosis (Bandak et al, 2017c;Eberhard et al, 2008) and chemotherapy and radiotherapy have been associated with long-term risk of Leydig cell dysfunction and manifest testosterone deficiency in patients with TGCC (Bandak et al, 2016). In the present study, ultrasonic size of testicle without a tumour evaluated at the follow-up was significantly smaller in patients with LCH, while there was no difference in the prevalence of microlithiasis among patients with or without LCH.…”
Section: Orchiectomy Alone Bep Radiotherapymentioning
confidence: 99%
“…Patients with TGCC are at risk of biochemical Leydig cell dysfunction manifested as increased serum levels of LH with or without corresponding low levels of testosterone and many of them will undergo treatment that can further impair the function of the remaining testicle (Sprauten et al, 2014;Bandak et al, 2016;Isaksson et al, 2017). We hypothesized that patients with Leydig cell hyperplasia (LCH) at the time of diagnosis were at increased risk of long-term Leydig cell dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported statistically increased risk of testosterone deficiency in TCS treated with orchidectomy plus ≤4 cycles of cisplatin-based chemotherapy, infradiaphragmatic radiotherapy or more extensive treatment, compared to TCS treated with orchidectomy alone (Bandak et al, 2016). A recent meta-analysis reported statistically increased risk of testosterone deficiency in TCS treated with orchidectomy plus ≤4 cycles of cisplatin-based chemotherapy, infradiaphragmatic radiotherapy or more extensive treatment, compared to TCS treated with orchidectomy alone (Bandak et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Furthermore, several populationbased studies or meta-analyses showed that a low serum testosterone level is a significant risk factor for developing cardiovascular disease. 8 The prevalence and severity of hypogonadism in chemotherapy-treated TC are varied among studies. However, some studies showed a higher risk of hypogonadism in survivors treated with chemotherapy compared with those treated with orchiectomy alone, 3,4 whereas others showed no difference between the two patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…5 On this point, a recently published meta-analysis showed that survivors treated with chemotherapy have a significantly higher risk for developing hypogonadism compared with survivors treated with orchiectomy alone. 8 The prevalence and severity of hypogonadism in chemotherapy-treated TC are varied among studies. [3][4][5] This might be partly due to differences in chemotherapy intensity and observation period.…”
Section: Introductionmentioning
confidence: 99%